Ginger oil (Zingiber officinale) in the fight against larvae of Contracaecum sp. that cause human zoonoses - Pavanelli, Gilberto Cezar; Nunes Simas, Islayla Paloma; Gonçalves, José Eduardo; de Brito Portela Castro, Ana Luiza (O Mundo da Saúde, 2018)
Anisakid nematode helminths have great importance in public health, with several reports of human infections caused by larvae of these parasites in several countries of the world. These parasites are common in freshwater and marine fish, with man as an accidental host. Contamination occurs when humans feed on raw fish in the form of sushi, sashimi, and ceviche, which are infected by the larval stages of these nematodes. In Brazilian rivers there are records of these larvae in Astyanax altiparanae (lambaris) and Geophagus brasiliensis (pearl cichlid), which are species widely distributed in the Neotropical region, especially in Brazil. These diseases are little-known by Brazilian health professionals because their frequency is still low, mainly due to the population’s low fish consumption and the difficulties medical professionals have in diagnosing them. The present study aimed to evaluate the larvicidal action of ginger essential oil (Zingiber officinale) on larvae of Contracaecum sp. removed from the visceral cavity of pearl cichlid and lambaris collected from the lake at Ingá Park, Maringá, PR, in the year 2016. Two hundred and thirty-four fish specimens were necropsied, and their larvae were tested to verify the larvicidal effect of ginger. Of these fish, 123 were parasitized, equivalent to 52.5%, of which 181 larvae were collected, all from the coelomic cavity. Ginger essential oil proved to be a promising larvicide, promoting larval death in vitro. This larvicidal action was observed at different times and concentrations, showing the efficacy of ginger oil in combating this zoonosis. It is suggested that new natural products be tested for this purpose, as the number of people who consume raw fish in Brazil continues to increase.